Growth and Body Composition of Spiny Lobster (Panulirus homarus) Reared with Short-Term Fasting - Pranawengrum Sekartadji; Arning Wilujeng Ekawati; Mohamad Fadjar (Jurnal Penelitian Pendidikan IPA, 2023)
Slow growth rate tends to be a challenge in the cultivation of spiny lobster (P. homarus) because it impact on long rearing periods and high operational costs, especially for feeds. Short-term starvation or fasting has known to allow the minimum feed usage without inhibiting biota growth, also improves digestive function, reduces the amount of water-soluble nutrient metabolites, and reduces operational costs. Spiny lobster (P. homarus) measuring 50.0 Â± 10.0 g was reared for 6 weeks in floating net cages. Lobsters were fasted at intervals of 1 fasting day/1 day of feeding, 1 fasting day/2 days of feeding, and fed daily. Survival, growth, and feed efficiency of spiny lobster (P. homarus) were analyzed. Higher growth rate and energy retention were found in spiny lobster (P. homarus) reared with short-term fasting system.Â  Lower FCR also found in the same rearing system. Spiny lobster (P. homarus) body content indicate its ability to store nutrient in mucle and hepatopancreas in order to adapt to starved condition. Short-term fasting can improve growth and feed efficiency in spiny lobster (P. homarus) cultivation